Induced Co-Deposition of Cu-Ge Alloys - Giovanni Zangari; Fu Zhao; Marcel Mibus (ECS Meeting Abstracts, 2016)
It is well known that some elements cannot be electrodeposited in pure form from aqueous solutions, but could instead be co-deposited with transition metals, forming alloys [1]. The codeposition of Fe, Ni, or Co with P, B, W, Mo and most recently Re have been reported and in most cases mechanisms have been proposed [2-5]. The induced codeposition of Ge however has been reviewed by Brenner in 1963 [1], but so far it has not been investigated in detail. Due to the potential importance of Cu-Ge alloys as candidate materials for next-generation interconnects, we have studied in detail their electrodeposition process from an alkaline tartrate-complexed electrolyte [6], and proposed an induced codeposition mechanism. Electrochemical processes occurring during the reduction of pure Cu, pure Ge and Cu-Ge alloys were studied by means of cyclic voltammetry (CV), electrochemical quartz crystal microbalance (EQCM) and electrochemical impedance spectroscopy (EIS) techniques. Cu reduction was found to be strongly inhibited at low overpotential by the addition of Ge in solution, due to the Ge 4+ reduction to GeOH, which is adsorbed at the electrode. At higher overpotentials, GeOH is reduced to GeH [7], which could be dissociated by surface Cu, forming a Cu-Ge alloy. Cu-Ge thin films were grown under potential control and their composition, phase, morphology and microstructure were investigated. Ge fraction in the alloys increases with the applied overpotential up to ~ 30 at%, resulting in a phase transition from face-centered cubic solid solutions (a-phase) to an ordered orthorhombic Cu 3 Ge intermetallic compound ( ɛ -phase). The dependence of resistivity on Ge content was also examined, showing a non-monotonic behavior. A minimum value was found for stoichiometric ɛ -Cu 3 Ge, displaying a resistivity of 7.5 μΩ cm -1 (~50 nm thickness) or 25 μΩ cm -1 (~1 μm thickness). The resistivity increase was linked to the slow but progressive incorporation of O into the films. References [1] A. Brenner “Electrodeposition of alloys: principles and practice” vol. II, Academic Press, New York, London, 1963, Chs. 33-36. [2] E.J. O’Sullivan “Fundamental and practical aspects of the electroless deposition reaction” in Advances in Electrochemistry and Electrochemical Engineering , vol. 7, R.C. Alkire, D.M. Kolb (eds), Wiley, 2001. [3] E. Gileadi, N. Eliaz; "The Mechanism of Induced Codeposition of Ni-W Alloys." ECS Transactions 2, 337 (2007). [4] E.J. Podlaha, D. Landolt “Induced codeposition I. An experimental investigation of Ni-Mo alloys” J. electrochem. Soc. 143, 885 (1996). E.J. Podlaha, D. Landolt “Induced codeposition II. A mathematical model describing the electrodeposition of Ni-Mo alloys” J. electrochem. Soc . 143, 893 (1996). [5] A. Naor, N. Eliaz, E. Gileadi. "Electrodeposition of alloys of rhenium with iron-group metals from aqueous solutions." J. electrochem. Soc . 157, D422 (2010). [6] A. Joi, R. Akolkar, U. Landau. "Pulse plating of copper germanide." Appl. Phys. Lett. 102, 134107 (2013). [7] X. Liang, Y.-G. Kim, D.K. Gebergziabiher, J.L. Stickney; “Aqueous electrodeposition of Ge monolayers” Langmuir 26, 2877 (2010).